Carcass and Meat Characteristics of Male Bali Cattle in Indonesian Smallholder Farms Fed Ration with Different Protein Levels - P. K. Tahuk; S. P. S. Budhi; Panjono Panjono; E. Baliarti (Tropical Animal Science Journal, 2018)
The objective of research was to determine the effect of different protein levels on the carcass and meat characteristics of male Bali cattle fattened in smallholder farms. The cattle used were 18 heads aged 2 to 2.5 years with initial body weight of 229.86±12.46 kg. The experimental cattle were randomly divided into 3 treatment groups i.e., T₀, T₁, and T₂. The T₀ group cattle were fed ration according to traditional practices of fattening cattle by farmers (100% forage). The T₁ group cattle were fed ration with 12% CP and 72% TDN. The T₂ group cattle were fed ration with 15% CP and 72% TDN. The variables measured were final body weight and the characteristics of the carcass (meat, fat, and ratio of meat to bone), and meat quality including the chemical composition of the meat (protein, fat, and collagen), meat tenderness, cooking loss, water holding capacity, and degree of acidity (pH). Data were analyzed by variance analysis. Results of research showed that the final body weight, and weight of carcass, meat, and fat of T₁ and T₂ groups were similar; conversely, those parameters in T₀ group cattle were lower (P<0.05) that those in T₁ and T₂ groups cattle. The meat protein content of T₁ and T₀ groups cattle were similar; conversely, T₂ group cattle had lower (P<0.05) meat protein content compared to T₁ and T₀ groups cattle.  Fat content of T₁ group of cattle was higher (P<0.05) than that of T₀ group; while moisture contents and cooking losses of T₀ group cattle were higher (P<0.05) compared to those of T1 and T₂ groups cattle. Collagen content of meat in T₁ group cattle was higher than (P<0.05) that in T₀ group cattle, but T₂ group cattle had similar meat collagen content to T₁ and T₀ groups cattle. Meat tenderness of T₁ group cattle was higher (P<0.05) compared to those of T₀ and T₂ group cattle. It is concluded that the male Bali cattle fed ration with 12% CP and 72% TDN can increase the carcass characteristics and meat quality. This proves that the productivity of male Bali cattle can be increased when fed ration with adequate protein with a balanced energy content.